Little seed [compact disc] : songs for children - Guthrie, Woody, 1912-1967 (Smithsonian Folkways Recordings, 2012)
In Little Seed, Elizabeth Mitchell embraces the gentle genius of America's musical bard Woody Guthrie, reminding us of how the loving bonds between parent and child endure and are strengthened through song. Moved by Guthrie's simple yet profound songs created for his daughter, and his ability to inhabit both the perspective of a loving, protective parent and the voice of a freewheeling child, Mitchell makes them her own, joined by family and friends to offer us a re-imagined rendition of classic.